An analogue of adenine that forms an "A:T" base pair of comparable stability to G:C. - Booth, J; Cummins, W; Brown, T (2004)
The heterocyclic base 7-aminopropargyl-7-deaza-2,6-diaminopurine (D) has been incorporated into oligodeoxynucleotides. D:T has similar thermodynamic stability to G:C and is a stable analogue of A:T.